Cervical carotid plaque evaluation using 3D T1-weighted black-blood magnetic resonance imaging: Comparison of turbo field-echo and turbo spin-echo sequences. Issue 5 (May 2016) - Inoue, Katsuhiro; Maeda, Masayuki; Umino, Maki; Takase, Shinichi; Yamahata, Tsunehiro; Sakuma, Hajime
Abstract: Purpose: To compare the capability of three-dimensional (3D) T1-weighted turbo field-echo (TFE) black-blood (BB) magnetic resonance imaging (MRI) and turbo-spin echo (TSE) BB MRI for discerning carotid plaques and the difference of signal intensities of the plaques from that of adjacent muscle in patients with cervical carotid stenosis. Methods: Cervical carotid stenosis was evaluated by 3.0-T MR in 43 patients (38 men and 5 women; age, 36–83 years; mean age, 70 years) during 8 months. The carotid BB MRI comprised 3D T1-weighted TSE BB (T1-TSEBB) and 3D T1-weighted TFE BB (T1-TFEBB) sequences. The delineation of the carotid plaque border was evaluated in comparison with digital subtraction angiography (DSA). The border between the plaque and vessel lumen was rated visually (4-point analysis) and quantitatively (contrast-to-noise ratio). The signal-intensity ratio (SIR) of the plaque to the adjacent muscle was also measured. Data of 3D T1-TSEBB and 3D T1-TFEBB were compared statistically using the Wilcoxon signed-rank test. Results: Visual and quantitative analyses revealed that the border between the plaque and vessel lumen was better delineated on 3D T1-TSEBB MRI than on 3D T1-TFEBB MRI (p < 0.01, respectively). SIR of the plaque-to-adjacent muscle was higher on 3D T1- TFEBB MRI than on 3D T1-TSEBB MRI (p < 0.05). High signal plaques with a SIR of >1.5 were underestimated on 3D T1-TSEBB MRI. Conclusions: 3D T1-TSEBB MRI was superior to 3D T1-TFEBB MRI for delineating carotid plaques; however, high signal plaques were underestimated on 3D T1-TSEBB MRI.